Karyotype plasticity in crickets: Numerical, morphological, and nucleolar organizer region distribution pattern of Anurogryllus sp. - Cristina Schneider, Marielle; Ariza Zacaro, Adilson; Ferreira, Amilton [UNESP]; Maria Cella, Doralice [UNESP] (Oxford University Press (OUP), 2010)
Within the Orthopteran species, those of the suborder Ensifera have been rarely studied from the cytogenetic point of view, mainly due to the difficulties for taxonomic identification of its species. The Gryllidae is the second largest family of this suborder and possesses some genera, such as Anurogryllus, that occur only on the American continents. The aim of this work was to determine the karyotype characteristics, the meiotic chromosome behaviour, and the nucleolar organizer region (NOR) pattern of Anurogryllus sp (Orthoptera: Gryllidae). In the analyzed sample, high levels of numerical, morphological, and NORs polymorphisms were detected. Within five distinct karyotypes that were found, the basic karyotype of Anurogryllus sp. showed 2n(♂) = 22 + X0 with acrocentric autosomes and a metacentric X sex chromosome; furthermore, a conspicuous secondary constriction related to the NOR was present along the entire short arm on pair 5. The other four types of karyotypes arose from centric fusions between elements of pairs 1/3, 2/6, 4/7 and a NOR partial translocation from pair 5 onto the long arm terminal region of one element of the fused pair 2/6. Such intraspecific variability and the consequences of high levels of polymorphism are discussed, leading to conjectures about the mechanisms that led to these chromosome rearrangements. © This is an open access paper. We use the Creative Commons Attribution 3.0 license that permits unrestricted use, provided that the paper is properly attributed.
Keywords: centric fusion; cytogenetic; meiosis; secondary constriction; translocation